Stepwise optimization and sensitivity improvement of green micellar electrokinetic chromatography method to simultaneously determine some fluoroquinolones and glucocorticoids present in various binary ophthalmic formulations. (16th July 2020) - Essam, Hebatallah M.; Saad, Martin N.; Elzanfaly, Eman S.; Amer, Sawsan M.
Abstract: A sensitive micellar electrokinetic chromatography method is presented to simultaneously quantify ofloxacin, gatifloxacin, dexamethasone sodium phosphate and prednisolone acetate. The method has the advantages of being rapid, accurate, reproducible, ecologically acceptable and sensitive. The electrophoretic separation utilized 20 mm borate buffer as background electrolyte with pH 10.0 ± 0.1 and 50 mm sodium dodecyl sulfate as a micelle forming molecule. A capillary tube (50 μm i.d., 33 cm) of fused silica was used and on‐column diode array detection at 243 nm for dexamethasone sodium phosphate and prednisolone acetate, and 290 nm for ofloxacin and gatifloxacin. Various factors were optimized such as the background electrolyte (type, concentration and pH), addition of sodium dodecyl sulfate and its concentration, detection wavelength, applied voltage and injection parameters. The studied drugs were efficiently separated in 6.2 min, at 20 kV with high resolution. The greenness of the method was estimated using an eco‐scale tool and the presented method was found to have excellent green characteristics. The method was validated in conformance with International Conference on Harmonization guidelines, with acceptable accuracy, precision and selectivity. The suggested method can be employed for the economic analysis of the four drugs in dissimilar binary combinations of eye drops saving solvents and chemicals.